Power exhaust by core radiation at COMPASS tokamak. (8th February 2021) - Komm, M.; Mancini, D.; Morbey, M.; Cavalier, J.; Adamek, J.; Bernert, M.; Bilkova, P.; Bohm, P.; Brida, D.; Février, O.; Henderson, S.; Hron, M.; et al.
Abstract: Substantial power dissipation in the edge plasma is required for the safe operation of ITER and next-step fusion reactors, otherwise unmitigated heat fluxes at the divertor plasma-facing components (PFCs) would easily exceed their material limits. Traditionally, such heat flux mitigation is linked to the regime of detachment, which is characterised by a significant pressure gradient between upstream and downstream scrape-off layer (SOL). However, the physics phenomena responsible for power dissipation and pressure loss are distinctly different, especially when the power dissipation is achieved by impurity seeding. In principle, it is possible to achieve substantial mitigation of the heat fluxes while maintaining conservation of the pressure along the open field lines in the SOL. This regime can be accessed by injection of medium- or high- Z impurities, which mostly radiate inside the last closed flux surface. The critical question related to such an approach is the effect on confinement and perspective fusion power generation in future thermonuclear reactors. In this work, we report on experiments at COMPASS tokamak, where neon and argon impurities were injected in ohmic or NBI-heated low confinement plasmas. With appropriate seeding waveform, stable scenarios were achieved, avoiding the radiative collapse of plasmas. Significant reduction of heat fluxes at the outer target was observed, with heat flux pattern similar to the one previously achieved by nitrogen seeding. The reduction of downstream pressure was, however, accompanied by an equal reduction of upstream pressure, indicating that the power dissipation occurred inside the separatrix. Indeed, the impurity cooling is causing a significant drop of edge temperature; however, the effect in the plasma centre is much less pronounced.